PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO KAOS POLOS MANIA CABANG SUKMAJAYA KOTA DEPOK - Ria Agustina; Cornelia Dumarya Manik (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of service quality and price on consumer satisfaction. The method used is a quantitative associative approach. The sampling technique used accidental sampling technique with the Slovin formula and a sample of 91 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that Service Quality influences Consumer Satisfaction with a coefficient of determination value of 66.6% and the hypothesis test obtained t count > t table or (13.319 > 1.988). Price has a significant effect on consumer satisfaction with a coefficient of determination value of 76.4% and the hypothesis test obtained t count > t table or (16.990 > 1.988). Service Quality and Price simultaneously have a significant effect on Consumer Satisfaction with the regression equation Y= 4.276 + 0.107X1 + 0.776X2. The coefficient of determination value is 76.7% while the remaining 23.3% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (144.516 > 3.10).